(untitled) (Modern information system and technologies, 2018)
To provide users with the necessary level of service from business applications, simplify the management of IT infrastructure, enhance security using its virtualization. In this work, an analysis of the properties of different types of this technology, with examples of software that implements them. The focus is on container virtualization using the Docker software.